Recent changes in pair abundance and breeding results in the main French populations of the Common Pochard Aythya ferina - Broyer, JoÃ«l (Wildfowl, 2019)
This study explored trends in Common Pochard Aythya ferina breeding abundance in four of the main breeding areas for the species in France (Dombes, Brenne, Forez, Sologne) since 1992. Systematic declines in the ratios of broods to the total numbers of pairs and in brood sizes of one-week-old families, contrasted with no clear changes in duckling survival between 1â€“3 weeks of age through the study period. Despite similar trends in reproductive measures, Pochard pair density varied unevenly across regions. In Forez, fish farming ceased at many ponds during the 1990s, where pair density initially increased but then declined. In Dombes and Sologne, pair density has apparently declined, whereas density increased in Brenne where ponds are still regularly stocked with fish for fish farming.